Dealing with bullies : a gospel response to the social disease of adult bullying - Arbuckle, Gerald A. (Strathfield, N.S.W : St. Pauls, 2003)
Bulling is a social disease of epidemic proportions. It occurs in many forms across a wide range of human relationships including those in families, workplaces and organisations, including the churches. Typically, this type of violence involves the abuse of power and provides malevolent satisfactions for perpetrators when they compel victims to submit to them. Further, it causes intimidation which can paralyse the lives and families of victim - and even destroys them. Bullying is a quality of most forms of violence, including racial, religious and sex-based discrimination; sexual, physical and psychological abuse, persecution and terrorism. The author describes what bullying is, how to recognise it and how it arises; and he offers practical steps for preventing it and dealing with it when it happens, whether we be victims ourselves or compassionate human beings who come to the assistance of victims. [back cover].
1.Adult bullying : definition and types/ --What does 'bullying' mean?/ --Bullying is an abuse of power/ --Bullying is an act of violence/ --Five common types of bullies in the workplace/ --Other types of bullying in the workplace and beyond/ --Summary/ --Questions/ --2.Bullies and victims/ --The characteristics of a bully/ --Sex differences in bullying/ --Prejudice, discrimination and bullying/ --The impact of bullying on victims/ --The similarity between suffering from bullying and Post-Traumatic Stress Disorder/ --Biblical reflections/ --Summary/ --Questions/ --3.Cultures of bullying/ --Defining 'culture'/ --Three models of cultures which promote bullying/ --Summary/ --Questions/ --4.A Gospel response/ --Five principles for preventing bullying/ --Five practical ways victims may respond to bullying/ --Five practical ways non-victims may assist victims/ --Summary/ --Questions
Includes bibliographical references
Keywords: Bullying; Bullying in the workplace; Bullying -- Religious aspects -- Catholic Church